Back to the Future for Influenza Preimmunity—Looking Back at Influenza Virus History to Infer the Outcome of Future Infections - Francis, Magen Ellen (Viruses, 2019)
The influenza virus-host interaction is a classic arms race. The recurrent and evolving nature of the influenza virus family allows a single host to be infected several times. Locked in co-evolution, recurrent influenza virus infection elicits continual refinement of the host immune system. Here we give historical context of circulating influenza viruses to understand how the individual immune history is mirrored by the history of influenza virus circulation. Original Antigenic Sin was first proposed as the negative influence of the host’s first influenza virus infection on the next and Imprinting modernizes Antigenic Sin incorporating both positive and negative outcomes. Building on imprinting, we refer to preimmunity as the continual refinement of the host immune system with each influenza virus infection. We discuss imprinting and the interplay of influenza virus homology, vaccination, and host age establishing preimmunity. We outline host signatures and outcomes of tandem infection according to the sequence of virus and classify these relationships as monosubtypic homologous, monosubtypic heterologous, heterosubtypic, or heterotypic sequential infections. Finally, the preimmunity knowledge gaps are highlighted for future investigation. Understanding the effects of antigenic variable recurrent influenza virus infection on immune refinement will advance vaccination strategies, as well as pandemic preparedness.